Implementasi Keperawatan Terapi Musik Pada Pasien Hemodialisa Dengan Masalah Keperawatan Ansietas - Agustin, Ismar; Putri, Prahardian; Muliyadi, Muliyadi; Lukman, Lukman; Azwaldi, Azwaldi; Firnanda, Dhea Lyra (JKM : Jurnal Keperawatan Merdeka, 2024)
Background : Hemodialysis is one of the therapies for patients with kidney failure to remove metabolic waste and excess body fluid by circulating blood into a device that consists of two compartments: blood and a dialyzer, to eliminate the metabolic waste and excess fluid. The repetitive hemodialysis process over an extended period can cause anxiety in patients. Method: This study utilizes a descriptive research design with a case study approach involving the nursing process. The case study subjects are two patients with kidney failure undergoing hemodialysis who are experiencing anxiety. Music therapy was administered three times during each hemodialysis session, with intervals based on the patients' preferences, over the course of three consecutive days. Case study techniques included conducting interviews/anamnesis, observations, and physical examinations. The instrument used to measure anxiety was the Hamilton Anxiety Rating Scale (HARS) questionnaire. Results: After the implementation of music therapy on both case study subjects, there was a decrease in anxiety levels. In subject 1, the initial measurement of anxiety was in the moderate category (HARS 24), and after the music therapy intervention, the anxiety level decreased to the mild category (HARS 16). In subject 2, the initial measurement of anxiety was also in the moderate category (HARS 26), and after the music therapy intervention, the anxiety level decreased to the mild category (HARS 18). Conclusion: The implementation of nursing music therapy can help reduce anxiety levels in hemodialysis patients